Analisis Anggaran Pendapatan dan Belanja Daerah (APBD) Pada Pemerintah Daerah Kabupaten Berau - Rahmawati Rahmawati (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2023)
Region Budget is an indicator of how well the region's performance is because it shows how a policy is planned for one fiscal year and the priorities it has. If the APBD is managed properly, then all regions get the dues, and compulsories can be utilized optimally for the benefit of the region and society. This study aims to analyze the magnitude of the growth rate of Sisa Lebih Perhitungan Anggarana and to identify and describe the factors that led to the occurrence of Sisa Lebih Perhitungan Anggaran (SiLPA) during the last five years in the financial statements of the Berau district government. This study is a quantitative descriptive study with a population of reports on the realization of the Berau District Budget for the 2017-2021 Fiscal Year. The sample in this study is in the form of excess budget calculations from revenue and expenditure budget data in the budget realization report of the Berau Regency APBD. The type of data used is secondary data sourced from the Berau Regency APBD realization report for the 2017-2021 Fiscal Year. Other results show that there is dependence on external funds, and the lack of quality of absorption of local budgets, causing dependence on fund management.